2009
DOI: 10.1158/0008-5472.can-08-3160
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Bacterial Vectors That Induce CD8+ T Cells with Similar Cytolytic Abilities but Disparate Memory Phenotypes Provide Contrasting Tumor Protection

Abstract: Induction of a functional CD8

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 47 publications
4
24
0
Order By: Relevance
“…to C57BL/6 mice with established B16-OVA melanoma and followed the tumor progression over time. Consistent with published work (17), LM-OVA led to enhanced tumor control and 25% eradication compared with LM-GP33-treated mice (Fig. 2C).…”
Section: Resultssupporting
confidence: 92%
“…to C57BL/6 mice with established B16-OVA melanoma and followed the tumor progression over time. Consistent with published work (17), LM-OVA led to enhanced tumor control and 25% eradication compared with LM-GP33-treated mice (Fig. 2C).…”
Section: Resultssupporting
confidence: 92%
“…Also, these bacteria are often used in combination with traditional methods such as radiation (4) and chemotherapy (25) for cancer therapy. Bacteria per se can stimulate immune responses (22) and secrete potential antitumor substances, DNA fragments, and other compounds that further improve the therapeutic effects (17,26). Therefore, interaction between bacteria and tumor cells and their antitumor effects have been extensively studied in recent years (9,12,43).…”
mentioning
confidence: 99%
“…While decreased CD62L expression on CD8 + T cells is associated with both effector and effector memory phenotypes and an overall increase in cytotoxicity, a predominantly CD62L high CD8 + T cell population has been associated with central memory and increased re-call CD8 + T cell proliferation and efficacious anti-tumor response [26]. After one vaccination of MS-OVA or LM-OVA causing an initial (day 7) induction of CD62L low effector CD8 + T cells, there was a subsequent gradual increase in CD62L high memory cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to generating a higher number of tumor specific CD8 + T cells, the memory phenotype is thought to be important for the overall anti-tumor immune response [26]. Previously, we have shown that when memory OVA-specific CD8 + T cell frequencies are similar and CD62L expression is low or their ligand is absent, long lasting tumor protection is impaired [26,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation